2017
DOI: 10.1016/j.physletb.2016.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Holographic research on phase transitions for a five dimensional AdS black hole with conformally coupled scalar hair

Abstract: In the framework of holography, we survey the phase structure for a higher dimensional hairy black hole including the effects of the scalar field hair. It is worth emphasizing that, not only black hole entropy, but also entanglement entropy and two point correlation function exhibit the Van der Waals-like phase transition in a fixed scalar charge ensemble. Furthermore, by making use of numerical computation, we show that the Maxwell's equal area law is valid for the first order phase transition. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
(46 reference statements)
0
11
2
Order By: Relevance
“…The disagreement between our findings and those in [5,6,[8][9][10][11][12][13][14][15][16][17][18] arises both from the fact that we have probed further away from criticality than had been done, and are thus finding larger relative errors, and also from a numerical argument. As noted in [7], when the areas given by (2.14) are compared, there is less of a relative error than for the more precise areas given by (2.11).…”
Section: )contrasting
confidence: 94%
“…The disagreement between our findings and those in [5,6,[8][9][10][11][12][13][14][15][16][17][18] arises both from the fact that we have probed further away from criticality than had been done, and are thus finding larger relative errors, and also from a numerical argument. As noted in [7], when the areas given by (2.14) are compared, there is less of a relative error than for the more precise areas given by (2.11).…”
Section: )contrasting
confidence: 94%
“…Very recently, the equal area law of HEE was proved to hold for the FPT in the HEE-temperature plane [22]. Based on [20], VDP phase transition of HEE in various AdS black holes have been studied in [23,24,25,26,27,28,29,30,31,32]. All of these works showed that the HEE undergoes the same VDP phase transition as that of the BHE.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Another confirmation of this similarity appear when we employ non-local observables such as entanglement entropy, Wilson loop, two point correlation function and the complexity growth rate [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Meanwhile, these tools are used extensively in quantum information and to characterize phases and thermodynamical behavior [40][41][42][43][44][45][46][47][48][49].…”
mentioning
confidence: 83%